Dilemmas in Military Medical Ethics: A Call for Conceptual Clarity - Rochon, Christiane (BioéthiqueOnline, 2015)
Despite the increase in and evolving nature of armed conflicts, the ethical issues faced by military physicians working in such contexts are still rarely examined in the bioethics literature. Military physicians are members of the military, even if they are non-combatants; and their role is one of healer but also sometimes humanitarian. Some scholars wonder about the moral compatibility of being both a physician and soldier. The ethical conflicts raised in the literature regarding military physicians can be organized into three main perspectives: 1) moral problems in military medicine are particular because of the difficulty of meeting the requirements of traditional bioethical principles; 2) medical codes of ethics and international laws are not well adapted to or are too restrictive for a military context; and 3) physicians are social actors who should either be pacifists, defenders of human rights, politically neutral or promoters of peace. A review of the diverse dilemmas faced by military physicians shows that these differ substantially by level (micro, meso, macro), context and the actors involved, and that they go beyond issues of patient interests. Like medicine in general, military medicine is complex and touches on potentially contested views of the roles and obligations of the physician. Greater conceptual clarity is thus needed in discussions about military medical ethics.